2021
DOI: 10.52462/jlls.3
|View full text |Cite
|
Sign up to set email alerts
|

The learnability of word knowledge aspects in Thai EFL high school learners

Abstract: This study investigated the learnability of multiple word knowledge aspects and the relationship between the word knowledge aspects. A total of 261 Thai high school students were measured on receptive and productive word knowledge aspects: word parts, the form-meaning link, and collocations. The current findings indicated that word parts are acquired first, followed by the form-meaning link and collocations, which suggest the receptive and productive continuum of learning word knowledge aspects. The present re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The three vocabulary knowledge tests were conducted on different days. Given that form knowledge can be transferred to other aspects (Webb, 2005;Laufer & Goldstein, 2004) and that 'use' knowledge is the last aspect that learners acquire (González Fernández & Schmitt, 2019;Nontasee & Sukying, 2021), the Word Segmentation Test was given first, followed by the L1 Translation test and, finally, the test of Word Part Use. Students were given all three tests and then received their instruction, which differed for the experimental and control groups.…”
Section: Data Collection Processmentioning
confidence: 99%
“…The three vocabulary knowledge tests were conducted on different days. Given that form knowledge can be transferred to other aspects (Webb, 2005;Laufer & Goldstein, 2004) and that 'use' knowledge is the last aspect that learners acquire (González Fernández & Schmitt, 2019;Nontasee & Sukying, 2021), the Word Segmentation Test was given first, followed by the L1 Translation test and, finally, the test of Word Part Use. Students were given all three tests and then received their instruction, which differed for the experimental and control groups.…”
Section: Data Collection Processmentioning
confidence: 99%
“…Vocabulary knowledge is a continuum of different sub-knowledge aspects (e.g., González-Fernández & Schmitt, 2019;Nation, 2013;Nontasee & Sukying, 2021). And that it consists of multiple levels of understanding, which range from knowing a word to using it in contexts (Henriksen, 1999;Laufer & Goldstein, 2004;Nation, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the field of the vocabulary knowledge construct and its acquisition and development have indicated that various aspects of vocabulary knowledge are interrelated and continually known (e.g., González-Fernández & Schmitt, 2019;Sukying & Nontasee, 2021), specifically receptive knowledge is first acquired and viewed to be built on productive knowledge (e.g., Hayashi & Murphy, 2011;Laufer & Goldstein, 2004;Sukying, 2022). However, learners had insufficient vocabulary knowledge, which inadequately relates to other skills of English language development, and they lacked exposure to the target vocabulary items.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the studies have been focused on the effect of language exposure on vocabulary development or learners' speaking performance (Akbarian et al, 2020;De Wilde et al, 2020;Muñoz, 2014;Nontasee & Sukying, 2021;Peters, 2018;Peters et al, 2019). The findings have revealed the positive effect of language exposure on learners' language proficiency.…”
Section: Introductionmentioning
confidence: 99%